Sport officials’ use of observational learning - Hancock, David J.; Rymal, Amanda M. (Frontiers in Sports and Active Living, 2024)
Observational learning is a key tool for improving skilled performances. Sport officials (e.g., referees, umpires, and judges) might glean particular benefits from using observation, as most officials do not engage in traditional practice. Unfortunately, little is known about how observational learning can be of benefit to sport officials. Thus, the purpose of this study was to take an exploratory approach to learn more about sport officials' use of observation. Participants included 206 sport officials (170 male, 35 female, 1 not specified) from 17 sports (mainly ice hockey, soccer, lacrosse, and volleyball). Sport officials completed a 50-question online survey regarding their use of observational learning. Survey questions revolved around the reasons for using observation (e.g., to learn about positioning or rule application), along with when and how participants used observation (e.g., before versus after competitions; watching an unskilled versus skilled model). Participants used observation most frequently to learn knowledge and application of rules, personality and game management, and fitness and positioning/mechanics. Results revealed that participants preferred to use observation after their competitions, while watching other sport officials in-person, and while observing a skilled model who was correctly executing their tasks. In the discussion, we expand on the results, connecting it to previous research in sport officiating or observational learning. Lastly, we offer suggestions for future researchers that should help build our understanding of sport officials' use of observation.